Electrochemical and optical CMOS sensors design for biochemical detection - Jiang, Yu (Nanyang Technological University, 2020)
Population ageing has driven the incremental demands on portable and cost-efficient point-of-care diagnostics. However, most of the existing techniques require bulky and expensive high-end instruments. New methods based on CMOS sensors are possible solutions.